Job Satisfaction and Performance of Certified Elementary School Teachers - Jakhontua Samuel Siburian; Arifin Siregar; Paningkat Siburian; Panigoran Siburian (IJECA (International Journal of Education and Curriculum Application), 2021)
The low level of teacher attendance, student national exam scores, and teacher performance assessment results are some indicators of low teacher performance. This article discusses the results of an explanatory survey of the phenomenon of low teacher performance aimed at knowing the effect of job satisfaction on the performance of 53 certified elementary school teachers. By using a questionnaire as a data collection instrument, which was analyzed using a simple regression analysis technique, the data analysis showed that job satisfaction had a positive and significant effect on the performance of certified teachers. To optimize teacher performance, school leaders must be fully concerned with teacher job satisfaction which is realized through promotion satisfaction, satisfaction with the work itself, salary satisfaction, work environment satisfaction, and supervision satisfaction in improving teacher performance.